2018
DOI: 10.4254/wjh.v10.i10.695
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric indicators of visceral adiposity as predictors of non-alcoholic fatty liver disease: A review

Abstract: The objective was to critically analyze studies that evaluated the predictive capacity of indicators of visceral adiposity in non-alcoholic fatty liver disease (NAFLD). The bibliographic research was carried out using the electronic database PubMed, LILACS and SciELO, references of selected articles. Although we found few studies, they have already used several indicators of visceral adiposity as waist circumference, waist-to-hip ratio, waist-to-height ratio, Lipid accumulation product, Body Shape Index, Body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
(61 reference statements)
0
21
0
1
Order By: Relevance
“…Obesity is an important underlying cause of NAFLD, and BMI is believed to be correlated with NAFLD 33 . WC is another anthropometric index that is a strong predictor of the presence of NAFLD 13,34 . As neither BMI nor WC could replace visceral fat adiposity as the most vital predictor of NAFLD 34 , we concomitantly used these two predictors for final adjustment and still found that they were highly independent predictors of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is an important underlying cause of NAFLD, and BMI is believed to be correlated with NAFLD 33 . WC is another anthropometric index that is a strong predictor of the presence of NAFLD 13,34 . As neither BMI nor WC could replace visceral fat adiposity as the most vital predictor of NAFLD 34 , we concomitantly used these two predictors for final adjustment and still found that they were highly independent predictors of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…WC is another anthropometric index that is a strong predictor of the presence of NAFLD 13,34 . As neither BMI nor WC could replace visceral fat adiposity as the most vital predictor of NAFLD 34 , we concomitantly used these two predictors for final adjustment and still found that they were highly independent predictors of NAFLD. Otherwise, obesity-related adipose tissue dysfunction or insulin resistance could contribute to a pro-inflammatory state with increased cytokines 35 .…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that BMI z ‐score and WHtR are more objective parameters than BMI and WC for diagnosing early liver steatosis and fibrosis in children. The WHtR is a non‐invasive, low‐cost, simple indicator, which can be easily interpreted and reproduced 22 . The CAP values also demonstrate a fair correlation with WHtR, even in the normal range of these parameters.…”
Section: Discussionmentioning
confidence: 93%
“…This is plausible as pancreatic volume and fatty liver assessment is usually done by ultrasonography or MRI that require precise imaging protocols and in such cases anthropometric indices may not be robust enough to quantify it. 25 We acknowledge the limitations of the study observations as MRI could not be performed on a large sample size of cases and controls due to reasons of economic feasibility. However, the study observations are worthy to be validated in other populations with larger sample sizes.…”
Section: Discussionmentioning
confidence: 99%